Glen Campbell [videorecording (DVD)] : I'll be me - Campbell, Glen, 1936-2017; Campbell, Glen, 1936-2017; Campbell, Kim (Kimberly Woollen) (Virgil Films, 2015)
They thought it would last five weeks. Instead it went for 151 spectacular sold out shows over a triumphant year and a half across America. What made this tour extraordinary was that Glen had recently been diagnosed with Alzheimer's disease. He was told to hang up his guitar and prepare for the inevitable. Instead, Glen and his wife went public with his diagnosis and announced that he and his family would set out on a "Goodbye Tour".